COVID-19 Rapid transformation of the medical on-call rotas to deal with the COVID-19 pandemic: a case study. Issue 1 (2021) - Aziz, Amir; Patel, Neel; Chakravorty, Trishna; Yan, May; Gull, David; Clare, Sarbjit; Varma, Chetan
No abstract available